A sociological study on generational crisis in relation to colonization system in Sri Lanka - Samarakoon, M.; Wijewardhana, B.V.N.; Wijethunga, W.T.D. (www.socialsciencejournal.in, 2018)
Wetlands for paddy production, were established in the dry zone of Sri Lanka as a solution to the lack of lands in rural areas. The history of colonies goes back to the arrival of King Vijaya. The first Aryans settled along Mahaweli, Walawe and Malwathu Oya rivers engaging in farming and animal husbandry as their livelihoods. But with the advent of the British in 1796 this agricultural economy converted into a plantation economy. As a result the production of paddy declined. In 1928, steps were taken to re-start development of these colonies and agricultural activities. This study ascertains a crisis compiled in the generational operating of the farming colonies. The objective of this study was to identify crisis and investigate the legality of land facilities, future conditions and changes in farming and agricultural use, for the coming generations. Five GN divisions in Anuradhapura district were selected and data were gathered through a structured questionnaire and formal/Informal interviews. The study show that 97% of the respondents earned income from other sources than their traditional agriculture. They were unable to reap the harvest and gain profit through cultivation due to severe problem of water scarcity. Within the current context, the land area used for agriculture was limited. Further, research findings shows that farmers expect future generations will work in other sectors than agriculture due to high competition within the educational system and high cost involved in the cultivation process.
Keywords: agriculture, colonies, crisis, economy, generation issues